Differential effects of oxytocin on social sensitivity in two distinct breeds of dogs (Canis familiaris). (December 2016) - Kovács, Krisztina; Kis, Anna; Pogány, Ákos; Koller, Dóra; Topál, József
Highlights: Breed-specific effects of oxytocin on dogs' social responsiveness were found. Genetic and epigenetic factors might contribute to differential oxytocin effects. Border Collies are more human oriented than Siberian Huskies. Oxytocin affects some social behaviors irrespective of breed. Sex differences can be found in the effect of oxytocin on dogs. Abstract: Dogs have been proven to show several human-analogue social behaviors, and recent research raises the possibility that the oxytocin system is related to these. However, despite dogs' general tendency to excel in the domain of social cognition, there is increasing evidence that dogs' ability to utilize human signals may vary with breed. Moreover, breeds may show differences not only in their 'inborn' communicative abilities, but also in their learning skills related to these. The aim of the present study was to explore breed differences and breed-specific effects of oxytocin administration on different aspects of social responsiveness. Dogs from two markedly different breeds, Border Collies (cooperative workers) and Siberian Huskies (independent workers) were tested. After having received intranasal administration of oxytocin or placebo, subjects participated in three behavioral tests measuring social responsiveness. Our results show that there are several behavioral differences between the two breeds and also that there are differential effects of the oxytocin treatment. Border Collies were in general more susceptible to the 'social' effects of oxytocin compared to Siberian Huskies: after oxytocin administration they (1) looked more at the experimenter in the 'Unreachable food' situation, (2) looked more at the owner and shifted their gaze more between the sound source and the owner in a potentially dangerous situation, and (3) looked longer at the experimenter's eyes in the 'Tolerance of prolonged eye contact' test. These findings suggest that selection for enhanced cooperative abilities, possibly complemented by the effect of different social environments the two breeds experience, affects dogs' performance in several behavioral tests and that the neurohormonal background differently modulates social behavior in different working breeds.